2009
DOI: 10.1021/ja907556q
|View full text |Cite
|
Sign up to set email alerts
|

Co-adsorption and Separation of CO2−CH4 Mixtures in the Highly Flexible MIL-53(Cr) MOF

Abstract: The present study attempts to understand the use of the flexible porous chromium terephthalate Cr(OH)(O(2)C-C(6)H(4)-CO(2)) denoted MIL-53(Cr) (MIL = Material from Institut Lavoisier) for the separation of mixtures of CO(2) and CH(4) at ambient temperature. The coadsorption of CO(2) and CH(4) was studied by a variety of different techniques. In situ synchrotron X-ray Powder Diffraction allowed study of the breathing of the solid upon adsorption of the gas mixtures and simultaneously measured Raman spectra yiel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
314
0
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 408 publications
(327 citation statements)
references
References 53 publications
11
314
0
2
Order By: Relevance
“…For more than a decade, lanthanide-based coordination polymers have attracted great attention, because of their fascinating topologies coupled with their potential applications in gas storage, [1][2][3][4][5][6][7][8] catalysis, [9] separation, [10] luminescence, [11][12][13][14][15][16] and molecular magnetism. [17][18][19] Because lanthanide ions are hard Pearson acids, [20,21] ligands that exhibit donor oxygen atoms have been extensively studied.…”
Section: Introductionmentioning
confidence: 99%
“…For more than a decade, lanthanide-based coordination polymers have attracted great attention, because of their fascinating topologies coupled with their potential applications in gas storage, [1][2][3][4][5][6][7][8] catalysis, [9] separation, [10] luminescence, [11][12][13][14][15][16] and molecular magnetism. [17][18][19] Because lanthanide ions are hard Pearson acids, [20,21] ligands that exhibit donor oxygen atoms have been extensively studied.…”
Section: Introductionmentioning
confidence: 99%
“…Owing to their many fascinating features, MOFs have shown promising performances over conventional adsorbents in separation of gas mixtures. 7,[22][23][24][25][26] Both experiments 27 and computational methods 28,29 have demonstrated that the introduction of polar functional groups in the frameworks significantly enhances the CO 2 adsorption capacity of MOFs. Moreover, MOFs with coordinatively unsaturated metal sites have been shown to adsorb increased amounts of CO 2 .…”
Section: Introductionmentioning
confidence: 99%
“…Some flexible PCPs showing gate-opening phenomena and stepped isotherms may be used to solve this problem; however, the real selectivities are usually much lower than those predicted by the singlecomponent isotherms because the non-preferred guest can also enter the opened channel above the gate-opening pressure 50 . We observed that the real C 2 H 6 /CH 4 selectivity (measured by mixed C 2 H 6 /CH 4 with 75:25 molar ratio) of O53 significantly increases from 92 to 140 at C 2 H 6 partial pressure from 4.7 to 5.5 bar, respectively, and remains 113 at C 2 H 6 partial pressure of 8.1 bar (Supplementary Methods and Supplementary Fig.…”
Section: Preparationmentioning
confidence: 99%